Strengthening local procurement in the Namibian Mining Industry - Kulula, Martin Itoolwa (My University, 2020)
This research aims to strengthen local procurement, a facet of backward linkages in the Namibian mining industry. This work emanates from Nickerson, et al., (2017) recent study on “The Relationship Between Local Procurement Strategies of Mining Companies & their Regulatory Environment: A comparison of South Africa and Namibia”. Their research concluded that, Namibia is faced with significant challenges in their efforts to increase local procurement in mining. Therefore, this research is part of further studies required in order to find solutions to these challenges. The research adopted a mixed methods explanatory sequential cross-sectional design. A sample consisting of six mines was selected and a study period of four years (2014 –2017) was chosen for this research. Local procurement in the mining industry is solely influenced by the Namibian Mining Charter, a document implemented in 2014, which is not legally binding. The Mining Charter defines local procurement as the buying of goods and services from Namibian owned businesses of choice. The Charter also has a 40% local procurement expenditure requirement for mining companies in the country. Stakeholders in the Namibian mining industry were found to have different definitions for local procurement, mainly due to lack of legally binding regulations to enforce a single definition. This has led to mining companies defining local procurement as buying of goods and services from Namibian registered businesses. A Namibian registered supplier encompasses a number of suppliers namely: local import agents, foreign exporter, locally based foreign manufacturer/service provider and local manufacturer/service provider. Some of these suppliers have limited value addition to the country. The adoption of this definition has therefore resulted in mining companies reporting inflated local procurement numbers for the period of study. Local procurement by five of the six mines selected for the research was found to be well above the mining charter target over the four years. However, upon closer analysis, it was discovered that most of the purchases by these mines were made from foreign owned Namibian registered businesses and reported as local procurement. This was the theme across all test samples and hence the inflated local procurement numbers. The procurement expenditure on Previously Disadvantaged Namibians’ (PDNs) owned businesses averaged at 2.8% for the period of study. This average cannot be ranked as there are no targets set for procurement from PDNs; however there is need for further research to be done in order to determine a target to be met by all mining companies every year. The researcher proposed a local procurement measuring and monitoring framework that will ensure that local procurement in mining is improved. The establishment of this framework will assist mining companies in developing effective supplier development programmes. Processes that needs to be undertaken in order to attain the desired framework outputs includes, accurately defining local procurement(based on varying combinations of three distinct aspects namely; participation, geographic location and value addition) and adopting a single definition for the industry. Other processes are design and development of local procurement regulations and policies, amending the Namibian Mining Charter and incorporating Social Impact Assessment (SIA) into core business strategies
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2020